PENGARUH DAYA TARIK, CITRA MEREK, KEAHLIAN DAN SELEBRITI ENDORSE TERHADAP MINAT BELI - Hana Krisdayanti; Eti Arini (UM. Bengkulu, 2022)
This study aimed to determine the effect of attractiveness, brand image, expertise and celebrity endorser toward purchasing interest of consumers on Fair and Lovely Advertising Version of Jessica Mila Agnesia. The population of this study were residents of the panoramic village, amounting to 95 people and sampling taken by using purposive sampling. The data collection technique of this study used questionnaire. The data was analysed by using instrument tests (test validity and reliability), multiple linear regression analysis, classical assumption test (multicollinearity normality and heteroscedasticity), coefficient of determination, t test and f test. Based on the results of multiple linear regression, the regression equation form Y= 12.711 + 0.392 (X1) + 0.243 (X2) + 0.278 (X3) + 0.797 (X4) This means that the variables of Attractiveness, Brand Image, Expertise and Celebrity Endorser have a positive effect toward toward purchasing interest of consumers on Fair and Lovely Advertising Version of Jessica Mila Agnesia. Meanwhile, from the hypothesis, the t-count value for Attractiveness (X1) is 2.746 with a significant level of 0.007, for Brand Image (X2) 1.995 with a significant 0.049, for Expertise (X3) 2.396 with a significant 0.019 and t-count for the Celebrity Endorser variable (X4) 6.675 with a significant 0.000. Thus, it means that the results of the t-test analysis state significant results for all variables and the hypothesis is accepted. The results of multiple regression analysis also show the coefficient of determination of 0.512, which means that the Attractiveness, Brand Image, Expertise and Celebrity Endorser variables effect toward purchasing interest of consumers by 51.2%, while 48.8% is influenced by other variables not observed in this study. Keywords: Attractiveness, Brand Image, Expertise, Celebrity Endorser and Consumer Buying Interest.